Examination of the Effects of Chronic Agomelatine Use on Pregnancy Time in Pre-pregnancy or in Different Periods of Pregnancy - Bulmus, Ozgur; Tan, Fatih; Sahinturk, Serdar; Zorlu, Gokhan; Serhatlioglu, Ihsan; Bulmus, Funda Gulcu; Kacar, Emine (Wiley, 2018)
[Abstract Not Available]